Differential effects of food availability and nest predation risk on avian reproductive strategies - Sofaer, Helen R. (2013)
Spatial and temporal variation in resource abundance and predation risk can favor the evolution of phenotypic plasticity as a means of tracking changing environments. However, because food abundance and predation risk often covary in nature, few studies have separated their effects or tested whether different phenotypic traits respond to the same sources of environmental variation. We investigated patterns of parental investment and behavior over a 7-year period in 2 island populations of orange-crowned warblers (Oreothlypis celata) that showed little genetic divergence but experienced dramatic temporal variation in rainfall and spatial variation in nest predation risk. The amount of rainfall in each year was correlated with food abundance, and birds on both islands initiated breeding earlier and laid larger clutches in wetter years. In contrast, the rate at which parents visited their nests was not affected by rainfall but was negatively correlated with nest predation risk both within and between islands. Our results suggest that although the effects of food availability and nest predation have been viewed as mutually exclusive drivers of entire suites of life-history and behavioral traits, these traits can differ in their sensitivity to resource abundance or mortality risk, and traits that are often correlated can be decoupled under appropriate environmental conditions.